MAKNA DAN NILAI PAPPASENG DALAM LONTARA’ LATOA KAJAO LALIDDONG DENGAN ARUMMPONE: ANALISIS HERMENEUTIKA - Rawe, Besse Tenri (JURNAL ILMU BUDAYA, 2020)
This study aims to explain the form, meaning, and value of pappaseng in Lontara 'Latoa: Kajao Laliddong with Arummpone by using Paul Ricouer's hermeneutic approach. This research is a qualitative research. The research data are in the form of Lontara 'Latoa: Kajao Laliddong and Arummpone texts. Data collection method used by the author is a library method by gathering information relevant to the topic or problem to be or is being studied. That information can be obtained from scientific books, research reports, scientific essays, theses and dissertations, regulations, provisions, yearbooks, encyclopedias, and written sources both printed and electronic. Data were analyzed using Paul Ricouer's hermeneutic analysis. The results of this study indicate the form of pappaseng in the form of dialogue discourse consisting of expressions and proverbs. The meaning of Pappaseng that was found consisted of three, namely the description of the characteristics of a good leader, a sign of the triumph of the state, and a characteristic of the destruction of the state. These three meanings gave birth to Bugis values including: honesty (alêmpureng), intellectual value (amaccangêng), firmness value (agêttêngêng), and family and love values (assiajingêng).